1986
DOI: 10.1111/j.1755-3768.1986.tb00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Fundus photography of width and intensity profiles of the blood column and the light reflex in retinal vessels

Abstract: Various optical properties of the fundus camera may have important implications regarding the use of photographs for image size measurements. By scanning across retinal vessels with a microdensitometer the width and the intensity characteristics of both the central light reflex and the streaming blood column may be measured. To establish a reliable basis for future measurements, we analysed the retina-to-film magnification, possible aberrations and the resolving power of our Zeiss camera. Furthermore, fundus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Retinal arteriolar widening has also been shown to be associated with retinopathy by several population studies. [ 21 , 22 ] A similar relationship was also investigated in the Multi-ethnic Study of Atherosclerosis (MESA), a prospective multi-ethnic population cohort who initially did not have baseline cardiovascular disease[ 23 ]. The MESA study demonstrated a significant association between wider retinal arteriolar calibre and increased risk of developing diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal arteriolar widening has also been shown to be associated with retinopathy by several population studies. [ 21 , 22 ] A similar relationship was also investigated in the Multi-ethnic Study of Atherosclerosis (MESA), a prospective multi-ethnic population cohort who initially did not have baseline cardiovascular disease[ 23 ]. The MESA study demonstrated a significant association between wider retinal arteriolar calibre and increased risk of developing diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxic exposure may affect the focusing precision of the photography. If so, an increase in standard deviation is expected in intensity measurements, but not in width meaurements (Brinchmann-Hansen et al 1986;Heier & Brinchmann-Hansen 1989). The objectivity of the technique will, however, not bias the results in any specific direction.…”
Section: Variability Of Resultsmentioning
confidence: 96%
“…We studied the width and the intensity profile of the central light reflex. The marking technique on the films, the scanning procedure, and the computerized data analysis have previously been described in detail (Brinchmann-Hansen & Engvold 1986a;Brinchmann-Hansen et al 1986;Heier & Brinchmann-Hansen 1989). Typical scan profiles across a retinal vessel is illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation